Medicinal Plants as a Potential and Successful Treatment Option in the Context of Atherosclerosis - Kirichenko, Tatiana V.; Sukhorukov, Vasily N.; Markin, Alexander M.; Nikiforov, Nikita G.; Liu, Ping-Yen; Sobenin, Igor A.; Tarasov, Vadim V.; Orekhov, Alexander N.; Aliev, Gjumrakch (Frontiers in Pharmacology, 2020)
Atherosclerosis is a chronic multifactorial disease characterized by mainly changes of blood lipids profile and inflammation in vessel wall. The cardiovascular disease based on atherosclerosis is currently the leading cause of mortality in developed countries. Therefore timely prevention and therapy of atherosclerosis are able to reduce the risk of the development of its clinical manifestations. Anti-atherosclerotic activity of medicinal plants mainly appears in their multiple effects such as anti-inflammatory, antioxidant, anti-atherogenic, hypotensive, lipid-lowering, anti-thrombotic. Moreover, most of medicinal plants are characterized by their pleiotropic anti-atherosclerotic action. In addition, the medicinal plants-derived pharmacological substances and/or compounds are characterized by relative safety and fewer side effects that allows considering them as one of potential anti-atherosclerotic effective agents. The direct anti-atherosclerotic effect of some medicinal plants was confirmed in clinical trials of carotid IMT progression during long-term medication with medicinal plants. This review attempted to determine the current status of the databases PubMed and Scopus (until November, 2019) to investigate the medicinal plants possessing anti-atherosclerotic activity in experimental and clinical studies.